KARAKTERISTIK KIMIA TEPUNG SILASE LIMBAH IKAN TUNA (Thunnus sp.) DENGAN PENAMBAHAN TEPUNG JAGUNG - Safitra, Safitra; Asnani, Asnani; Rejeki, Sri (Universitas Halu Oleo, 2020)
Chemical characteristics of Silage Flour from Tuna Fish Waste (Thunnus sp.) with cornflour additionABSTRACT The purpose of this study was to determine the chemical characteristics and the effect of the addition of cornflour to tuna waste silage flour. This study used a Completely Randomized Design (CRD) consisting of four treatments, namely TS1 (5% addition to corn flour), TS2 (10% adding corn flour), TS3 (15% adding corn flour), TS4 (20% adding cornflour) ) and repeat three times. Data from observations were analyzed using ANOVA (Analysis of Variance) at a level of 95%, if there is a real difference (P> 0.05) then a further test was performed with a DMRT (Duncan Multiple Range Test) tests at a 95% level. The results showed that the effect of adding cornflour to fish waste silage flour had a significant effect on the chemical content test value. The results of the chemical test of the silage flour show water content between 10.4% -8.4%, ash content of 24.2% -7.9%, protein content of 47.5% -43.3%, and fat content of 4.6 % -2.1%. Keywords: Silage flour, tuna waste (Thunnus sp.), Cornflour and proximate composition.ABSTRAKTujuan penelitian ini adalah untuk mengetahui karakteristik kimia dan pengaruh penambahan tepung jagung pada tepung silase limbah ikan tuna. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) yang terdiri dari empat perlakuan yaitu perlakuan TS1 (5% penambahan tepung Jagung), TS2 (10% penambahan tepung jagung), TS3 (15% penambahan tepung jagung), TS4 (20% penambahan tepung jagung) dan ulangan sebanyak tiga kali. Data hasil pengamatan dianalisa menggunakan ANOVA (Analysis of Variance) pada taraf 95%, apabila terdapat beda nyata (P>0,05) maka dilakukan uji lanjut dengan uji DMRT (Duncan Multiple Range Test) pada taraf nyata 95%. Hasil penelitian yang diperoleh menunjukkan bahwa pengaruh penambahan tepung jagung pada tepung silase limbah ikan memberikan pengaruh nyata terhadap nilai uji kandungan kimia. Hasil uji kandungan kimia tepung silase menunjukkan kadar air antara 10,4%-8,4%, kadar abu 24,2%-7,9%, kadar protein 47,5%-43,3%, dan kadar lemak 4,6%-2,1%.Kata kunci: Tepung silase, limbah ikan tuna (Thunnus sp.), tepung jagung serta komposisi proksimat